Their "Kampf" [motto : The Germans must be submitted to an education in civilisation just as they have submitted to the opposite of civilisation: Hitlerism] (Poona : Dabholkar Bros. Press, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; Duitsland